COVID‐19 in Australia: our national response to the first cases of SARS‐CoV‐2 infection during the early biocontainment phase. Issue 1 (11th February 2021) - Shaban, Ramon Z.; Li, Cecilia; O'Sullivan, Matthew V. N.; Gerrard, John; Stuart, Rhonda L.; Teh, Joanne; Gilroy, Nicole; Sorrell, Tania C.; White, Elizabeth; Bag, Shopna; Hackett, Kate; Chen, Sharon C. A.; et al.
Abstract: Background: On 31 December 2019, the World Health Organization recognised clusters of pneumonia‐like cases due to a novel coronavirus disease (COVID‐19). COVID‐19 became a pandemic 71 days later. Aim: To report the clinical and epidemiological features, laboratory data and outcomes of the first group of 11 returned travellers with COVID‐19 in Australia. Methods: This is a retrospective, multi‐centre case series. All patients with confirmed COVID‐19 infection were admitted to tertiary referral hospitals in New South Wales, Queensland, Victoria and South Australia. Results: The median age of the patient cohort was 42 years (interquartile range (IQR), 24–53 years) with six men and five women. Eight (72.7%) patients had returned from Wuhan, one from Shenzhen, one from Japan and one from Europe. Possible human‐to‐human transmission from close family contacts in gatherings overseas occurred in two cases. Symptoms on admission were fever, cough and sore throat ( n = 9, 81.8%). Co‐morbidities included hypertension ( n = 3, 27.3%) and hypercholesterolaemia ( n = 2, 18.2%). No patients developed severe acute respiratory distress nor required intensive care unit admission or mechanical ventilation. After a median hospital stay of 14.5 days (IQR, 6.75–21), all patients were discharged. Conclusions: This is a historical record of the first COVID‐19 cases in Australia during the early biocontainment phase of the national response. These findings were invaluable for establishing early inpatient and outpatient COVID‐19 models of care and informing the management of COVID‐19 over time as the outbreak evolved. Future research should extend this Australian case series to examine global epidemiological variation of this novel infection.